COMMUNICATIVE LANGUAGE TEACHING IN ENGLISH LANGUAGE TEACHING: THEORETICAL FOUNDATIONS, PRACTICAL APPLICATIONS, AND CONTEMPORARY PEDAGOGICAL PERSPECTIVES - Mahmudjonova Ezoza Zafar qizi (TADQIQOTLAR, 2026)
Abstract: Communicative Language Teaching (CLT) has emerged as one of the most influential and widely adopted methodological paradigms in the field of English Language Teaching (ELT) over the past five decades. Rooted in sociolinguistic and functional theories of language, CLT prioritizes the development of communicative competence over mere grammatical accuracy, thereby fostering learners» ability to use language meaningfully in real-life contexts. This paper provides a comprehensive examination of CLT»s theoretical underpinnings, tracing its origins from Chomsky»s distinction between linguistic competence and performance to Hymes»s communicative competence framework and Halliday»s functional linguistics.